2021
DOI: 10.3390/jpm11050398
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Analysis of 3D Dose Distributions to Predict Toxicity of Radiotherapy for Cervical Cancer

Abstract: Standard treatment for locally advanced cervical cancer (LACC) is chemoradiotherapy followed by brachytherapy. Despite radiation therapy advances, the toxicity rate remains significant. In this study, we compared the prediction of toxicity events after radiotherapy for locally advanced cervical cancer (LACC), based on either dose-volume histogram (DVH) parameters or the use of a radiomics approach applied to dose maps at the voxel level. Toxicity scores using the Common Terminology Criteria for Adverse Events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Developing predictive models for radiation-induced toxicity is crucial for optimizing radiotherapy dosages and enhancing patients' quality of life [14]. Artificial intelligence can predict potential complications in the rectum and bladder, such as proctitis and cystitis, by learning from previous cases [15].…”
Section: Predictive Modeling For Radiation-induced Damagementioning
confidence: 99%
“…Developing predictive models for radiation-induced toxicity is crucial for optimizing radiotherapy dosages and enhancing patients' quality of life [14]. Artificial intelligence can predict potential complications in the rectum and bladder, such as proctitis and cystitis, by learning from previous cases [15].…”
Section: Predictive Modeling For Radiation-induced Damagementioning
confidence: 99%
“…Being amenable to further refinements to maximize the heart sparing in left breast cancer irradiation, 3D-CRT is the most preferred and debated RT technique among the radiation oncologists treating these patient cohorts [ 9 , 10 ]. The dose-volume histogram (DVH) can verify quantitative assessment of the absorbed dose for the target and critical organs, and biological indexes such as the tumor control probability (TCP) and normal tissue complication probability (NTCP) also can predict the likelihood of radiation-induced complications in normal tissues and the local control rate of tumors [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is convenient, providing fast computations and general image-guided therapy structure to support clinical conversion of experimental therapeutic methods and has been used in a lot of radiotherapy-related researches. [14][15][16] Segmentation and quantification using 3D Slicer can help analyze results from the MC simulation. A study on radiosynoviorthesis 17 had demonstrated the feasibility of segmentation and quantitation of radiological features on 3D MRI, where MC simulation was used to find the effective treatment range and S-value.…”
Section: Introductionmentioning
confidence: 99%
“…SlicerRT 13 is a free and open‐source extension available, which is intended for radiation therapy purposes. It is convenient, providing fast computations and general image‐guided therapy structure to support clinical conversion of experimental therapeutic methods and has been used in a lot of radiotherapy‐related researches 14–16 …”
Section: Introductionmentioning
confidence: 99%